Implementing person-environment approaches to prevent falls: A qualitative inquiry in applying the Westmead approach to occupational therapy home visits - Clemson, L.; Donaldson, A.; Hill, Keith; Day, L. (Wiley-Blackwell Publishing Asia, 2014)
Background/aims: Despite evidence of the effectiveness of home safety interventions for preventing falls, there is limited uptake of such interventions within community services. Therefore, as part of a broader translational project, we explored issues underlying the implementation of an evidence-based home safety fall prevention intervention. Method: We conducted in-depth interviews with eight occupational therapists and two programme coordinators engaged to deliver a home safety fall prevention intervention. Six community health centres within two metropolitan regions of Melbourne, Australia participated. The RE-AIM framework and Diffusion of Innovations theory underpinned the interviews which examine the enablers and barriers to implementing a home safety fall prevention intervention and integrating it into routine community preventive practice. Analysis involved thematic and content analysis. Results: Investment in the home safety for fall prevention intervention was supported and valued by coordinators and therapists alike, and a number of themes emerged which influenced implementation of this intervention. These included issues of: compatibility with organisational processes, individual practitioner practices and skills, a prevention approach, and client expectations; relative advantage in terms of flexibility of the process, client engagement and regional capacity building; complexity of implementing the intervention; and observability related to the invisible nature of fall prevention outcomes. Conclusion: Implementation of this home safety fall prevention intervention was influenced by a range of interrelated organisational, practitioner and client related factors. The findings from this project provide insights into, and opportunities to increase the sustainable implementation of the home safety fall prevention intervention into practice.